O Ensino de Números fracionários: problemas e perspectivas - Araújo, Maria José (2010)
The main purpose of the present study is to identify potential problems, limitations and prospects in the teaching of fractional numbers in the 5th and 6th years of primary education, focusing on observation and analysis of the methodological approaches adopted by teachers of a Cajazeiras basic education school, to analyze how the contents related to fractional numbers are taught in these years. In particular, we verify if the teaching practices of teachers promoted the application of that knowledge to the content of other disciplines or to real-world situations or whether they referred to them. In order to achieve these objectives, we have developed a qualitative research, based on a case study, aiming to expand our understanding on the causes of learning difficulties of students, considering the methodological practice of the teacher. In our theoretical framework, we have used the contributions of several authors, such as: Nunes and Bryant (1997), Merlini (2005), Moutinho (2005), Silva (1997), Santos (2005), Toledo and Toledo (1997), among others, who have developed studies on fractional numbers. Field research was conducted at first by applying a questionnaire to two professors, research subjects, in order to describe their profile. Secondly, we have analyzed the textbooks used in class by those teachers, linking them with the content of their lesson plans and, finally we have also observed the classes given by those teachers. Our analysis revealed that improved training in mathematics by students of basic education, particularly those belonging to primary school, does not depend on individual actions, but on a set of actions which aim dynamism in the teaching of mathematics. The objective of the pedagogical knowledge of the teacher is to lead students to realize that mathematics is part of their daily lives, since mathematical elements are always present in the social-cultural context of the student, which promote the understanding of such elements, that is, allow the construction of meaning to what the student learns. The elaboration of meanings helps to establish the relationship between mathematical concepts and their applicability in situations outside the classroom. It is important to present mathematical knowledge to students as historically constructed and constantly evolving, as opposed to the most frequently used practice in mathematics teaching.